2013
DOI: 10.1037/a0032447
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the effectiveness of intelligent tutoring systems on K–12 students’ mathematical learning.

Abstract: In this study, we meta-analyzed empirical research of the effectiveness of intelligent tutoring systems (ITS) on K-12 students' mathematical leaming. A total of 26 reports containing 34 independent samples met study inclusion criteria. The reports appeared between 1997 and 2010. The majority of included studies compared the effectiveness of ITS with that of regular classroom instmction. A few studies compared ITS with human tutoring or homework practices. Among the major findings are (a) overall, ITS had no ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
3
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(113 citation statements)
references
References 46 publications
1
94
3
4
Order By: Relevance
“…In addition, in the case of conventional instruction, as opposed to problem-centered instructional models, meta-analysis indicated that computer-based scaffolding including intelligent tutoring systems positively impacted students' learning (g = 0.66) regardless of instructor's effects, study types, and region (Kulik and Fletcher 2016). Other meta-analyses on the effectiveness of intelligent tutoring systems showed a wide range of effect sizes: g = 0.41 among college students (Steenbergen-Hu and Cooper 2014), g = 0.09 for K-12 students' mathematical learning (Steenbergen-Hu and Cooper 2013), d = 0.76 when compared the effectiveness with humantutors (VanLehn 2011), and d = 1.00 for scaffolding within an early model of intelligent tutoring systems (Anderson et al 1995). However, no meta-analyses have investigated the effectiveness of computer-based scaffolding in the context of problem-based learning.…”
Section: Meta-analyses Related To Computer-based Scaffoldingmentioning
confidence: 99%
“…In addition, in the case of conventional instruction, as opposed to problem-centered instructional models, meta-analysis indicated that computer-based scaffolding including intelligent tutoring systems positively impacted students' learning (g = 0.66) regardless of instructor's effects, study types, and region (Kulik and Fletcher 2016). Other meta-analyses on the effectiveness of intelligent tutoring systems showed a wide range of effect sizes: g = 0.41 among college students (Steenbergen-Hu and Cooper 2014), g = 0.09 for K-12 students' mathematical learning (Steenbergen-Hu and Cooper 2013), d = 0.76 when compared the effectiveness with humantutors (VanLehn 2011), and d = 1.00 for scaffolding within an early model of intelligent tutoring systems (Anderson et al 1995). However, no meta-analyses have investigated the effectiveness of computer-based scaffolding in the context of problem-based learning.…”
Section: Meta-analyses Related To Computer-based Scaffoldingmentioning
confidence: 99%
“…Three recent reviews reported no real improvement in school performance due to the use of ITSs (Slavin, Lake, & Groff, 2009;Steenbergen-Hu & Cooper, 2013;U.S. Department of Education, Institute of Education Sciences, What Works Clearinghouse, 2009).…”
mentioning
confidence: 96%
“…O trabalho de meta-análise de Ma e colegas [65] não encontrou diferenças significativas no desempenho dos alunos na aprendizagem com STIs e a aprendizagem através de tutoria humana, quando o sistema realiza uma seleção individualizada de problemas, prompts e feedbacks que são entregues ao aprendiz. Por fim, os estudos de meta-análise descritos em [58,59] também encontraram que os STIs podem ser tão efetivos quanto um professor particular.…”
Section: Sistemas Tutores Inteligentesunclassified